And then there were none : a mystery play in three acts - Christie, Agatha, 1890-1976.; Christie, Agatha, 1890-1976. (New York : S. French, 2004)
Ten people find themselves stranded in the lonely house on Indian Island when their supposed hosts send word that they have been detained. A mysterious voice, afterwards discovered to come from a gramophone record, indicts each on of them -- the eight guests and the two servants -- of murder. It transpires that no-one has met their hosts and that they have evidently been decoyed to the island. First one and then another dies; each death according to the rhyme of "Ten little Indians, " and with each death one of the little china figurines on the mantelpiece is found broken. The tension grows as they realize that the killer is, in fact, one of themselves. Eventually only two little Indians are left; the real killer appears (his death having been feigned) and the remaining two are able to outwit him--Publisher's description.
Earlier editions published under the title: Ten little Indians.
A dramatization of the author's novel: "And then there were none." New York, 1940.
"#118"--p. [4] of cover.
Keywords: English drama; Mystery plays; English drama